Human HLA prolongs the host inflammatory response in Streptococcus suis serotype 2 infection compared to mouse H2 molecules - Ni, Chengpei; Han, Yi; Wang, Yajing; Ma, Ting; Sha, Dan; Xu, Yanan; Cao, Wenting; Gao, Song (Frontiers in Cellular and Infection Microbiology, 2023)
Streptococcus suis (S. suis) is widely acknowledged as a significant zoonotic pathogen in Southeast Asia and China, which has led to a substantial number of fatalities in both swine and humans. Despite the prevalent use of mice as the primary animal model to study S. suis pathogenesis, the substantial differences in the major histocompatibility complex (MHC) between humans and mice underscore the ongoing exploration for a more suitable and effective animal model. In this study, humanized transgenic HLA-A11/DR1 genotypes mice were used to evaluate the differences between humanized HLA and murine H2 in S. suis infection. Following intravenous administration of S. suis suspensions, we investigated bacterial load, cytokine profiles, pathological alterations, and immune cell recruitment in both Wild-type (WT) and humanized mice across different post-infection time points. Relative to WT mice, humanized mice exhibited heightened pro-inflammatory cytokines, exacerbated tissue damage, increased granulocyte recruitment with impaired resolution, notably more pronounced during the late infection stage. Additionally, our examination of bacterial clearance rates suggests that HLA-A11/DR1 primarily influences cell recruitment and mitochondrial reactive oxygen species (ROS) production, which affects the bacterial killing capacity of macrophages in the late stage of infection. The reduced IL-10 production and lower levels of regulatory T cells in humanized mice could underlie their compromised resolution ability. Intervention with IL-10 promotes bacterial clearance and inflammatory regression in the late stages of infection in transgenic mice. Our findings underscore the heightened sensitivity of HLA-A11/DR1 mice with impaired resolution to S. suis infection, effectively mirroring the immune response seen in humans during infection. The humanized HLA-A11/DR1 mice could serve as an optimal animal model for investigating the pathogenic and therapeutic mechanisms associated with sepsis and other infectious diseases.